The SMHP™ position statement on therapeutic carbohydrate reduction for type 1 diabetes - Tro Kalayjian; Beth J. McNally; Matthew W. Calkins; Mark T. Cucuzzella; Robert Cywes; Hayden Dikeman; David T. Dikeman; Evelyne Bourdua-Roy; Sarah M. Rice; Ian Lake; Laura A. Buchanan; Douglas B. Reynolds; et al. (Journal of Metabolic Health)
This article presents the position of the Society of Metabolic Health Practitioners (SMHP) regarding therapeutic carbohydrate reduction (TCR) nutrition interventions for type 1 diabetes mellitus (T1DM). A modified Delphi methodology was used to arrive at a consensus consisting of several focus groups, multiple rounds, and an anonymous survey. The field of endocrinology has seen many new advances for the treatment of T1DM including hybrid closed-loop insulin delivery systems and continuous glucose monitors for better glycaemic control, monoclonal antibodies to delay the onset of disease and increased access to paediatric endocrinologists, among many other noteworthy achievements. Despite these advancements, standard of care approaches to T1DM result in higher than acceptable morbidity and mortality, with a high prevalence of microvascular and macrovascular complications. Insulin resistance in type 1 diabetes is an independent risk factor for adverse outcomes even in well controlled type 1 diabetes. In 2021, only 21% of adults with T1DM in the United States achieved the American Diabetes Association’s (ADA’s) target haemoglobin A1C goal of 7.0%, while data in the paediatric and adolescent population have demonstrated worse glycaemic control. Supported by observational and interventional evidence, the SMHP advocates for the reevaluation of the prevailing nutritional therapy for T1DM with more broad consideration for TCR. The SMHP recommends open access and clinical support for TCR nutrition interventions for individuals with T1DM of all ages and calls upon the medical community to help foster more attention and research on TCR for T1DM.